Restrictive Policies on Huawei During the Donald Trump Administration: An Analysis of U.S. National Security and Geopolitical Interests - Roissyam, Anja Yanuar; Nugroho, Bambang Wahyu (Universitas Muhammadiyah Yogyakarta, 2023)
The trade war that occurred between United States and China extended to the technology sector. The two countries are competing in the development of 5G networks. China, through Huawei, which is a pioneer in the development of 5G networks, has faced confrontation from the U.S. government by ban Huawei from operate their business in North America. This article will discuss about the restriction policy on Huawei by the United States of America during Donald Trump's presidency. The United States places restrictions on Huawei based on suspicious that 5G network developed by Huawei can be misused by China government as an espionage tool. This article attempts to analyze the reasons that led to the United States during Donald Trump's presidency imposing restrictive policies on a telecommunications company from China, Huawei. In this article the authors used a qualitative explanatory research method. In analyzing the restriction policy against Huawei, researchers use the concept of national interest and national security concept. Researchers found that the United States placed restrictions on Huawei because the 5G network developed by Huawei might be misused by the Chinese government as and espionage tool against the United States state, companies, and people so that it has the potential to threaten the national security of the United States. Also, through this restriction policy, the United States intends to stem China's hegemony in geopolitical information. Hopefully, this article will provide new insight for future discussion about restriction policy by the United States to Huawei.